WCRP and WWRP THORPEX YOTC (Year of Tropical Convection) Project ... - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2010)
The realistic representation of tropical convection in our global atmospheric models is a long-standing grand challenge for numerical weather forecasts and global climate predictions. Our lack of fundamental knowledge and practical capabilities in this area leaves us disadvantaged in modeling and predicting prominent phenomena of the tropical atmosphere such as the ITCZ, ENSO, TBO, monsoons and their active or break periods, the MJO, subtropical stratus decks, near-surface ocean properties, easterly waves, tropical cyclones, bulk budgets of cloud microphysical quantities, and even the diurnal cycle. Furthermore, tropical weather and climate disturbances strongly influence stratospheric-tropospheric exchange as well as the extratropics, with the later mediated via poleward migration of synoptic systems or through initiating Rossby wave trains that can involve a range of processes and time scales.To address the challenge of tropical convection, WCRP and WWRP/THORPEX propose a Year of coordinated observing, ...